Development of a smart apps creator-based e-book to enhance students' conceptual understanding and digital literacy - Tsania Nur Diyana; Francisca Happy Artanti (Momentum: Physics Education Journal, 2025)
This study aims to develop a Smart Apps Creator-based e-book that is feasible and effective for use in learning the topic of measurement in Grade 10 high school. In addition, this study aims to determine the improvement of students’ conceptual understanding and digital literacy after using the physics e-book developed with Smart Apps Creator. The method used in this research is Research and Development (R&D) using the 4D development model. Data collection techniques in this study included non-test instruments such as observation and questionnaire sheets, as well as a 27-item multiple-choice test on the measurement topic. The results showed that: (1) The e-book learning media based on Smart Apps Creator is suitable for use in learning the topic of measurement for Grade 10 high school students, with the category "Very Good"; (2) The e-book learning media based on Smart Apps Creator can improve students’ conceptual understanding (N-gain = 0.75) with the category "High"; (3) The Smart Apps Creator-based e-book learning media can improve students’ digital literacy (N-gain = 0.58) with the category "Upper Medium"; and (4) The Smart Apps Creator-based e-book learning media is effective for learning the topic of measurement to enhance students’ conceptual understanding and digital literacy.